Interrogating the effects of bullying amongst early childhood education learners: case of Chikurubi Prison Primary School in Epworth/ Mabvuku/ Tafara district (EPMAFARA) - Bondera, Lucia (Midlands State University, 2018)
The researcher carried out a study on how parents were involved in their children’s academic learning through homework with grade one learners at Nhamburiko Government School in Mabelreign-Warren Park District. The study will assist the researcher, parents and teachers to know the views of parents regarding homework. The reviewed literature answered the research questions in the order they were presented. The researcher used qualitative research design which enabled her to use questionnaires and interviews to collect data. Data presentation was done through the use of themes. The analysis, interpretations and discussions deriving from the data were subsequently carried out. The sample for the study was made up of nine parents of grade one green. The findings of the study revealed that parents participated in their children’s homework even though some had challenges with the new curriculum and did not have the required text books. The researcher recommended that the school should engage parents in children’s homework through workshops. The school was also recommended to partner with corporate world in order to get assistance for purchasing new curriculum text books and materials to use.